Plan de negocios compañía asesora de marketing y programación para estaciones radiales: radio estation development solutions - Morales, D. (2009)
The project idea was born when a discomfort and widespread dissatisfaction of radio listeners and citizens in general about radio programming was identified. This context led us to analyze the different possibilities and measures that radio stations could adopt to improve their programming and marketing and brand strategies often non-existent. We found a business opportunity offering advising and auditing services non exploited niche by using a methodical process involving a series of marketing researches and the key knowledge in marketing, strategic planning, musical programming and experience in radio business. All this key factors make us capable of improving the stations programming making their content more attractive for the radio listeners. RADIO ESTATION DEVELOPMENT SOLUTIONS would become the strategic associate of the radio stations offering them opportunities of improvement and growth by means of a constructed, measurable, permanent and objective process, of investigations and advices to design a corporate image and effective programming based on primary updated information.